2005
DOI: 10.1042/bj20050981
|View full text |Cite
|
Sign up to set email alerts
|

Transport of polyamines in Drosophila S2 cells: kinetics, pharmacology and dependence on the plasma membrane proton gradient

Abstract: Polyamine transport activities have been described in diverse multicellular systems, but their bioenergetic mechanisms and molecular identity remain unclear. In the present paper, we describe a high-affinity spermine/spermidine transport activity expressed in Drosophila S2 cells. Ion-replacement experiments indicate that polyamine uptake across the cell membrane is Na+-, K+-, Cl-- and Ca2+-independent, but pH-sensitive. Additional experiments using ionophores suggest that polyamine uptake may be H+-coupled. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…More specifically, a library of polyamine-anthracene conjugates was found to possess similar PAT selectivity and toxicity profiles in mammalian cell culture and Drosophila imaginal discs. Furthermore, polyamine uptake in Drosophila S2 cells was found to be sensitive to pH in another independent study [97]. That Drosophila could be used for the screening of compounds with known bioavailability was reported in a recent study [22].…”
Section: Drosophila In Drug Uptake and Bioavailabilitymentioning
confidence: 93%
“…More specifically, a library of polyamine-anthracene conjugates was found to possess similar PAT selectivity and toxicity profiles in mammalian cell culture and Drosophila imaginal discs. Furthermore, polyamine uptake in Drosophila S2 cells was found to be sensitive to pH in another independent study [97]. That Drosophila could be used for the screening of compounds with known bioavailability was reported in a recent study [22].…”
Section: Drosophila In Drug Uptake and Bioavailabilitymentioning
confidence: 93%
“…In this work, candidate substrates that might be transported by CCC9a included amino acids (Glu and Asp especially) as also described for other PA carriers (Rinehart and Chen, 1984;Jack et al, 2000;Kashiwagi et al, 1992;Uemura et al, 2005b;Romero-Calderon and Krantz, 2006) as already alluded to above. One could thus predict that CCC9a operates as a PA-amino acid efflux system-preliminary studies have confirmed that PA fluxes in HEK huCCC9a could be elicited in both directions-unless the chemical potential for PA, Glu, and Asp was balanced off by that of another (still unidentified) substrate or the electrical potential.…”
Section: Discussionmentioning
confidence: 95%
“…Many PA transporters have been shown to promote the comovement of ions and amino acids or to exhibit ion-dependent PA transport activity (Rinehart and Chen, 1984;Jack et al, 2000;Kashiwagi et al, 1992;Kobayashi et al, 1992Kobayashi et al, , 1999Uemura et al, 2005b;Romero-Calderon and Krantz, 2006). As such, we determined whether PA transport activity in stable HEK huCCC9a was affected by such cosubstrates and whether it varied with (PA) according to Michaelian behavior as would be expected it was induced by a carrier system.…”
Section: Effect Of Cosubstratesmentioning
confidence: 90%
See 1 more Smart Citation
“…Polyamine uptake has been shown to be temperature-dependent in a variety of cells (Basselin et al, 2000;Fukumoto and Byus, 1996;Romero-Calderon and Krantz, 2006;Soulet et al, 2002).…”
Section: Putrescine and Spermidine Uptake Into Isolated P Falciparummentioning
confidence: 99%